Internationalisation and Mode Switching Performance, Strategy and Timing - Sachse, Uwe.; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Managing an international operation is seen by many as one of the most challenging activities in an enterprise. Uwe Sachse offers substantial answers to the question of how companies behave after they have entered a particular foreign market. The results of the empirical study show that the mode switch is an important option for improving performance in foreign markets. Uwe Sachse shows that, over the duration of foreign business activity, companies pursue characteristic internationalisation pathways through their choice of mode.
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems